Plant diversity storage and ecotourism values of Sibalom Natural Park benefit transfer approach. - Mooc, Emy Marie
Sibalom Natural Park (SNP) in Antique, Philippine is a protected area proclaimed through Proclamation No.282, series of 2000 and with its various features, benefits can be derived there from - both use and non-use values. Economic valuation is a way to determine and quantify these benefits. With no published economic valuation studies conducted in SNP, this study determined the values of the functional benefits and ecotourism values derived from Sibalom Natural Park using benefit transfer - unit value transfer approach. Primary economic valuation studies were reviewed and selected and used as study sites that are comparable or similar to Sibalom Natural park (policy site). Adjusting the important differences between the study and policy sites, this resulted to 813,783.48 PHP per species per year for plant diversity storage value, 15, 506.99 PHP per visit per year and 319.22 PHP per visitor per year for ecotourism values of Sibalom Natural Park.